A Path-Planning Algorithm Using Vector Potential Functions in Triangular Regions - Pamosoaji, A. K.; Keum-Shik Hong (IEEE transactions on systems, man, and cybernetics. Systems, 2013)
A path-planning algorithm for a complex workspace split into triangular regions is investigated. The algorithm, which is formulated to achieve a goal configuration subject to the desired goal-point orientation, generates a collision-free region-to-region-compliant path. To that end, a set of vector potential functions is used. These functions are calculated using information on the triangular regions' vertices, the obstacles' positions, and the goal configuration. Path-planning procedures based on these constraint-satisfying functions are constructed. The proposed path-planning method, entailing velocity-and-orientation tracking control and configuration control, is applied to a unicycle vehicle, and its performance is compared with that of an existing path-planning scheme.